Effect of Burnishing Load on Surface Roughness and Wear Behaviour of ZE41 Magnesium Alloy - S.K. Baral; M.M. Thawre; B.R. Sunil; Ravikumar Dumpala (Archives of Metallurgy and Materials, 2025)
Magnesium (Mg) alloys have become an attractive choice for lightweight structural applications. However, improving the tribological characteristics of Mg alloys is essential to widen the range of applications. In the present work, ball burnishing was performed with different burnishing loads from 40 N to 80 N to investigate its effect on surface roughness, microhardness, and wear resistance. It was found that the 50 N burnishing load exhibits the best surface finish with a reduction of 46.2% in surface roughness compared to unburnished alloy. The highest microhardness was observed at 60 N load with an improvement of ~35.5%. Higher loads beyond 50 N resulted in increased surface roughness. Higher burnishing load caused surface distortion and flaking which decreased the microhardness beyond 60 N load. At 50 N burnishing load, better wear resistance with a reduction of ~40% was achieved compared to unburnished alloy. Improvement in surface finish and microhardness are responsible for better wear resistance. Worn surfaces exhibited abrasion, oxidation, and delamination wear mechanisms in the unburnished sample. Whereas, delamination wear was absent in the burnished specimen at 50 N burnishing load.